Surface hardness evaluation of a 3D printable resin designed for final restorations - Rodrigues, Bruno Trivelato; Paraguassu, Selene Paiva; Freitas, Dora Isabel de Sousa Martins; Ishikiriama, Sérgio Kiyoshi; Maenosono, Rafael Massunari (Brazilian Dental Science, 2024)
Objective: Advancements in the digital area have triggered significant interest among researchers in recent years, particularly concerning 3D printers. In dentistry, 3D printers are already employed to create dental models, surgical guides, and provisional restorations. Recently, a new 3D printable resin has been introduced with the aim of being used for final restorations (BioCrown, Makertech Labs). Despite its innovative nature, there is considerable interest in the physical and mechanical properties of this new class of material. This study aimed to evaluate the surface hardness of this new resin, comparing it to well-known materials such as acrylic resin for provisional restorations (Triunfo Dent’s, Triunfo), conventional composite resin for final restorations (Z250, 3M ESPE), and 3D printable resin for provisional restorations (BioProv, Makertech Labs). Methods: Knoop microhardness testing was conducted (n = 10), and data were analyzed using the Kruskall-Wallis test, followed by the Dwass-Steel-Critchlow-Fligner test for individual comparisons (p < 0.05). Results: Higher hardness values (kgf/mm2) were observed for BioCrown (17.4 ± 2.5) compared to the conventional acrylic resin group (14.5 ± 1.5), but no differences were found for BioProv (17.8 ± 1.5). The conventional composite resin group obtained the highest hardness values (81.3 ± 5.4). Conclusion: It can be concluded that the new 3D printable resins for final restorations exhibit low hardness levels, which may indicate inferior performance as final restorations, especially when compared to conventional composite resins. Further studies are necessary to comprehend and enhance the mechanical properties of 3D printable resins.KEYWORDSBioprinting; Composite resins; Permanent dental restoration; Hardness tests; Three-dimensional printing.